Guided Imagery Strategy to Improve Student’s Reading Comprehension in English Department at Universitas Nias Year 2020/2021 - Elwin Piarawan Zebua (EDUKASIA: Jurnal Pendidikan dan Pembelajaran, 2021)
Reading is the skill every university students have to master. However, the reading skill especially reading comprehension of the 3rd semester students of English Department at IKIP Gunungsitoli had not yet achieved the stated minimum achievement score. It was difficult for them to comprehend a reading text of the reading comprehension itself. Thus, the problem was decided to be solved through a classroom action research by using the Guided Imagery Strategy. The purposes are to find out whether the strategy can improve their reading comprehension and to discover the factor/s that influences the improvement. There were 27 students as the subject of the research, especially the class B of the 3rd semester of English Department at IKIP Gunungsitoli, year 2020/2021. The research was conducted in 3 cycles with five meetings of each cycle. The data was gathered through the observation sheets, field notes, interviews, tasks and tests. The result of the research revealed that the Guided Imagery Strategy could improve the subjects’ reading comprehension. The data showed that the students’ average score and target of success were increased each cycle. The average score in cycle I was 52,6 (59,2% target of success), then increased up to 71,1 in cycle II (66,6% target of success) and 81,1 in cycle III (81,4% target of success). Furthermore, the factors that influenced the improvement were material, media, classroom activities, classroom management, teaching strategy and teacher’s approach. Summing up, the Guided Imagery Strategy gave positive improvement toward the students’ reading comprehension.